Impact of HPV Vaccination on the Incidence of High-Grade Cervical Intraepithelial Neoplasia (CIN2+) in Women Aged 20–25 in the Northern Part of Norway: A 15-Year Study - Marte Pettersen Mikalsen; Gunnar Skov Simonsen; Sveinung Wergeland Sørbye (Vaccines, 2024)
Background: Human papillomavirus (HPV), the most prevalent sexually transmitted infection globally, is a key risk factor for high-grade cervical lesions and cervical cancer. Since 2009, HPV vaccination has been part of the national immunization program for girls in 7th grade in Norway (women born 1997 and later). This study aimed to assess the impact of HPV vaccination on the incidence of high-grade cervical precursors (CIN2+) among women aged 20–25 in Troms and Finnmark over a 15-year period. Materials and Methods: In this time series study, we analyzed cervical screening data from 15,328 women aged 20–25 in Troms and Finnmark, collected between 2008 and 2022. Statistical methods, including linear and logistic regression, were employed to evaluate changes in cervical intraepithelial neoplasia grade 2 and worse (CIN2+) incidence and compare risks between vaccine-offered cohorts and pre-vaccine cohorts. Results: The incidence of CIN2+ initially increased from 31 cases per year in 2008 to 110 cases in 2018, then significantly decreased to 44 cases per year by 2022 ( p < 0.01). Women in pre-vaccine cohorts had a substantially higher risk of CIN2+ (OR 9.02, 95% CI 5.9–13.8) and CIN3+ (OR 19.6, 95% CI 7.3–52.6). Notably, no vaccinated women with CIN2+ tested positive for HPV types 16 or 18. Furthermore, none of the 13 cervical cancer cases recorded during the study were from the vaccinated cohorts. Interpretation: The findings suggest a significant reduction in the incidence of high-grade cervical precursors following the introduction of the HPV vaccine in Norway’s national immunization program, highlighting its effectiveness in cervical cancer prevention among young women in Northern Norway.